Problems and Progress in Defining Terrorism in International Law - Ridarson Galingging (Fakultas Hukum Universitas Gadjah Mada, 2009)
There is an effort to adopt an internationally-accepted legal definition for ‘terrorism’ since such definition will enhance international cooperation in fighting terrorism, which at the moment is fragmented and ineffective. However, various obstacles e.g. political heterogeneity or ideological discrepancy arise when seeking a uniformed definition of terrorism, hence this study. Dunia internasional berupaya untuk menetapkan definisi legal ‘terorisme’ yang diterima secara umum karena definisi ini dapat meningkatkan kerjasama internasional dalam melawan terorisme yang saat ini masih terkotak-kotak dan tidak efektif. Tulisan ini membahas pelbagai kesulitan yang muncul dalam upaya mencari definisi tersebut, seperti masalah keragaman politik dan kesenjangan ideologi antarnegara.